Investigation Obstacles (Obstruction of Justice in the Crime of the Planned Killing of Brigadir Nofriansyah Yosua Hutabarat in Legal Criminology Perspective) - Erseta, Marcella; Pratama, Dicky Mulya; Tobing, Ega Yolanda Lumban; Alexander, Johan; Hasian, Clarissa; Azhar, Muhammad Dzaky Chairy (Lex Prospicit, 2024)
Obstruction of justice carried out by the police group is an example that in practice anyone who violates the law must be punished. This research will examine this matter from a criminological point of view and discuss the sociological, psychological and biological impacts of the perpetrators of obstruction of justice as well as the role of society viewed through the crime side of the disappearance of evidence. This study uses a normative juridical research method. The results showed that this case was categorized as premeditated murder, which according to Sigmund Freud's psychoanalytic theory, psychologically, Ferdy Sambo committed the act of this crime of murder was due to a stimulus from Brigadier Yosua as the victim, while Ferdy Sambo's subordinates or subordinates committed this crime of murder because there were environmental factors (police agencies) that provided an opportunity to cause a crime. Criminology has a relationship with and is closely related to criminal law, especially when discussing Obstruction of Justice, so in this case it will discuss the existence of criminal etiology which seeks to explain that criminology is a tool for carrying out an effective arrangement and control of a legal sanction against criminal law which has the aim is to give fear to those who have the intention to commit a crime or a violation of criminal law. In this case, the police must be able to show that the police institution is at the forefront in handling all cases of criminal acts indiscriminately and prove this to the public.